Djulis Hull Improves Insulin Resistance and Modulates the Gut Microbiota in High-Fat Diet (HFD)-Induced Hyperglycaemia - Yu-Tang Tung; Jun-Lan Zeng; Shang-Tse Ho; Jin-Wei Xu; I-Hsuan Lin; Jyh-Horng Wu (MDPI AG, 2021)
In this study, we annotated the major flavonoid glycoside, rutin, of djulis hull crude extract using a Global Natural Products Social Molecular Networking (GNPS) library and its MS/MS spectra. To evaluate the protective effect of djulis hull crude extract and rutin on glucose tolerance, we fed mice a high-fat diet (HFD) for 16 weeks to induce hyperglycaemia. These results showed that crude extract significantly decreased HFD-induced elevation in the area under the curve (AUC) of weekly random blood glucose and oral glucose tolerance tests (OGTT), homeostasis model assessment (HOMA-IR), and advanced glycation end product (AGE) levels, and significantly increased pIRS1 and Glut4 protein expression in epididymal white adipose tissue (eWAT) and liver. Furthermore, the HFD-induced reduction in the activity of glutathione peroxidase (GPx) and catalase (CAT) was reversed by crude extract. In addition, ZO-1 and occludin protein expression in the colon was markedly downregulated in HFD-fed mice, resulting in decreased intestinal permeability and lipopolysaccharide (LPS) translocation, but were restored following crude extract. Moreover, the crude extract intervention had a profound effect on the alpha diversity and microbial community in the gut microbiota. Therefore, djulis hull crude extract could improve blood glucose and increase insulin receptor sensitivity in HFD-induced hyperglycaemia, which is likely due to its modulation of the gut microbiota, preservation of the integrity of the intestinal barrier to reduce body inflammation, increased antioxidant activity, and modulation of insulin signalling.